Exploration of social representations about vocation, profession and work of high school students - Najar Santa Cruz, Kenia Briset (2022)
Research with a qualitative approach and phenomenological design, whose main objective was to explore the content of social representations about vocation, profession and work of high school students. The sample consisted of eight Peruvian students, between 15 and 17 years of age, in fourth and fifth grade of high school from public and private schools. The data collection technique was the semi-structured interview. It was found that the participants are making their professional decisions based on social imaginaries that do not reflect the complexity of the current reality. Vocation, profession and work present similar functions for young people, linked to the development of educational and/or work activities. Specifically, the profession is linked to an educational training that grants a certain rank and identity, the job constitutes a means of economic income for subsistence and the vocation implies pleasure and involves only personal aspects, but not social ones.